2005
DOI: 10.1262/jrd.51.87
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ovary Storage Time and Temperature on DNA Fragmentation and Development of Porcine Oocytes

Abstract: Abstract. The present study was conducted to investigate the effects of storage time and temperature of porcine ovaries on the quality and nuclear maturation in vitro of oocytes obtained from stored ovaries and their subsequent development after in vitro fertilization. The ovaries were stored in physiological saline for 0, 3, 6, 9 and 12 h at various temperatures (4, 15, 25 and 35 C). The pH of follicular fluid obtained from the ovaries, DNA fragmentation of the oocyte nucleus and meiotic competence of oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 36 publications
3
74
1
9
Order By: Relevance
“…These findings are in agreement with those reported by Love et al (2003) and Yuge et al (2003), but contrast those of Wongsrikeao et al (2005) and Evecen et al (2010). Some disparities might be caused by long storage time, which was studied by these investigators.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are in agreement with those reported by Love et al (2003) and Yuge et al (2003), but contrast those of Wongsrikeao et al (2005) and Evecen et al (2010). Some disparities might be caused by long storage time, which was studied by these investigators.…”
Section: Resultssupporting
confidence: 92%
“…Lack of suitable buffers resulted in pH decreases, which increased fragmented DNA nuclei significantly. It was suggested that the plasma membrane of oocytes was highly permeable to H + ions without any regulatory mechanism (Wongsrikeao et al, 2005). If external pH was maintained by increasing buffering capacity, the expulsion of protons would continue for a prolonged period, thus reducing the drop in intracellular pH buffers (Salehi et al, 2004), which has biological importance in determining the net electric charge of amino acids, which affects cell membrane permeability (Patel et al, 1973).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Storage at a warmer temperature conditions increased the percentage of porcine oocytes with DNA fragmented nuclei by altering the follicular pH and resulted in a lower rate of oocyte in vitro maturation. Wongsrikeao et al (2005) observed that storage of porcine ovaries at 4°C to 35°C for 6 h decreased the pH of follicular fluid and induced DNA frag- Within a column, groups with the same letter are not significant different (P < 0.05) *indicates that groups are not highly significantly different (P < 0.01) . Porcine oocytes have been described to be very sensitive to chilling, leading to a reduction in membrane integrity in oocytes stored < 15°C (Didion et al, 1990;Yuge et al, 2003).…”
Section: Discussionmentioning
confidence: 99%